International communication dynamics of American intervention efforts to democratize in the arab spring through forward strategy for freedom in the middle east - Fika Nurislamia; Ej Syamsy Asriya (Association for Scientific Computing Electrical and Engineering (ASCEE), 2019)
This papera aims to describe how international communication dynamics of America to response of Arab Spring. Arab Spring is an event that shocked the world when the Middle East flared up. The demonstrators took to the streets to demand an authoritarian regime downgrade and replace it with democracy. The democratization process that took place in the Middle East was in the world spotlight. America is considered a country that intervenes so that democratization can be realized in the Middle East. This is supported by various American interests in the Middle East. By using research library data search methods, the authors get the results of the form of intervention carried out by America to realize democratization in the Middle East.